Bridging the Gender Gap in P2P Lending: How Financial and Digital Literacy with Entrepreneurial Orientation Drive MSME Success - Mahastanti, Linda Ariany; Rita, Maria Rio; Sitorus, Destri Sambara (Jurnal Manajemen Bisnis, 2025)
Research Aims: This study investigates the impact of peer-to-peer (P2P) lending on the financial performance of micro, small, and medium enterprises (MSMEs) in Central Java, Indonesia, with a focus on gender-based sub-samples. While previous research has recognized P2P lending as an alternative financing source, this study uniquely explores the antecedent roles of financial literacy, digital literacy, and entrepreneurial orientation, and their consequences for financial performance.Design/Methodology/Approach: The research was conducted in Semarang Regency, Salatiga Municipality, and Surakarta Municipality, regions characterized by strong access to P2P platforms. Using purposive sampling, data was collected from 333 MSME respondents with prior P2P lending experience. Partial Least Squares Structural Equation Modeling (PLS-SEM) with moderation and a mediation analysis was employed to examine the relationships.Research Findings: The findings revealed that financial literacy and entrepreneurial orientation significantly influence P2P lending usage, whereas digital literacy does not. Gender does not generally moderate the relationships; however, a sub-sample analysis revealed that financial literacy plays a stronger role for women than men in accessing P2P lending. This indicates that female entrepreneurs rely more heavily on financial knowledge when making borrowing decisions. Overall, P2P lending use positively contributes to MSME performance.Theoretical Contributions/Originality: This study extends the Resource-Based View (RBV) Theory, conceptualizing financial and digital literacy as intellectual resources and entrepreneurial orientation as a strategic resource that enhances performance.Practitioner/Policy Implications: Policymakers must enhance MSME capabilities through financial literacy, entrepreneurial orientation, and digital literacy, in ensuring informed decisions, sustainable growth, innovation, adaptability, and stronger economic resilience.Research Limitations/Implications: A limitation included the lack of influence of digital literacy, suggesting that future research should incorporate the government’s role in addressing data security issues.